PEMBELAJARAN PENCATATAN SIKLUS AKUNTANSI BAGI SISWA-SISWI SMAN 95 JAKARTA MELALUI KEGIATAN MBKM - Lianih, Septia Meta; Salim, Susanto (Jurnal Serina Abdimas, 2024)
In the current era of industrial revolution 4.0, we must be ready for all forms of change, including technological developments. Technological developments are one of the reasons for changes in accounting science such as accounting software. The development of this technology certainly helps accountants in carrying out accounting records more quickly and efficiently. However, the emergence of accounting software was not well received by everyone. The development of technology in accounting science is a threat for some people due to the idea that the role of humans will be easily replaced by technology itself. To handle these changes, a good understanding of accounting knowledge is needed so that the role of accountants is not easily replaced. Teaching assistance activities in educational units are a form of implementation in increasing students' understanding of accounting science. The teaching assistance activity at SMAN 95 Jakarta which was held from 4 September to 16 November 2023 aims to foster students' understanding of the accounting cycle at SMAN 95 Jakarta. Teaching assistance activities apply several learning methods such as understanding the material, question and answer activities, practice questions and discussion activities as well as distributing questionnaires to students. The results of teaching assistance activities at SMAN 95 Jakarta are considered very good. The results of the data obtained from distributing questionnaires to students show an average that is considered 'very good' which can indicate that teaching assistance activities at SMAN 95 Jakarta are running well and have a positive influence on students' understanding of accounting.